Sebuah Implementasi Teknik Trim and Crop Comp Dalam Pembuatan Animasi 3D Motion Graphic - Dwi Rahayu; Sri Mulyatun; Khalida Zulfannisa Sutrisno (Universitas PGRI Yogyakarta, 2023)
Many motion graphics techniques have been developed. Now motion graphics are not only in the form of 2D animation, several techniques can change a 2D illustration image or design into a 3D object. This development is of course due to the need for an object that needs to be displayed in 3D to clarify the intent of the design being conveyed. 3D motion graphic techniques can be created using preset, plugins, effects, or simply using various object layers that are processed using masking techniques. In this research, we will discuss techniques for making 3D motion graphics with a case study of an object that rotates the moon and the earth on its axes. The application of the trim and crop comp technique to create 3D animation objects can be developed with other animated objects. This research involved more than 10 of the best tutorials on YouTube as study material and tested to find simple techniques that are easy for beginners to use. The results of the study of the tutorial will be tested for its effectiveness on 160 students who are beginners in learning animation. Hopefully, this technique will not only be learning material for beginners but can also be developed and applied to other objects to facilitate further animation learning.